EMBEDDING MENTAL HEALTH AND PSYCHOSOCIAL SUPPORT IN NIGERIA'S GOVERNANCE SYSTEMS: PATHWAYS TO SUSTAINABILITY IN A RAPIDLY CHANGING SOCIETY - Omojugba Victor Olusoye; Tolulope Adebola Yamah; Samson Olukunmi Olaoye (Universitas Negeri Makassar, 2026)
Despite the enactment of Nigeria's National Mental Health Act (2023), the country's governance response to its mental health burden remains structurally inadequate. Approximately 20% of Nigerians live with a diagnosable mental health condition, yet fewer than 10% receive minimally adequate care. Nigeria specific institutional frameworks for sustainable psychosocial support integration across health, education, and social protection sectors remain conspicuously absent from both policy and academic literature. This paper addresses that gap by examining pathways for embedding mental health and psychosocial support (MHPSS) within Nigeria's governance architecture. The study is guided by the Walt and Gilson Policy Triangle and anchored in the WHO Comprehensive Mental Health Action Plan 2013-2030 and SDG Target 3.4. Adopting an integrative critical policy analysis design, the study systematically reviews peer reviewed literature alongside Nigerian legislative documents and international frameworks including the IASC Guidelines on Mental Health and Psychosocial Support. The review identifies persistent structural barriers. These include weak inter sectoral coordination, chronic underfunding, and a critically insufficient mental health workforce operating at 0.16 psychiatrists per 100,000 population against the WHO benchmark of 1.0. Stigma driven exclusion renders existing legislation normatively progressive but operationally insufficient. Evidence from comparable low and middle income country contexts demonstrates that multi sectoral MHPSS governance strengthens institutional capacity, enhances community resilience, and supports the attainment of SDG Targets 3.4, 10.2, and 16.6. The paper proposes a five pillar governance framework anchored in policy coherence, decentralised service delivery, intersectoral accountability, community based task shifting, and sustainable financing. This framework offers a replicable and contextually adaptive model for MHPSS integration in Nigeria and analogous sub Saharan African governance contexts.